Analisis Persepsi Masyarakat Milenial Terhadap Kualitas Pelayanan Pasar Tradisional Dengan Infrastruktur Sebagai Variabel Intervening - Ria Manurung; Suyudi Suyudi (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2019)
Banyumas Regency is supported by several business sectors and the largest contribution from the trade sector. To improve the trade sector, infrastructure improvements are carried out through market revitalization. Banyumas Regency has 92 modern markets and 26 traditional markets. The formulation of the problem is how the factors of the tendency of the millennial society towards the quality of traditional market services and how infrastructure can strengthen or weaken the tendency of millennial society towards the quality of traditional market services in improving the functioning of the market. The research method is descriptive qualitative analysis with the type of field research Primary data obtained from questionnaires as many as 310 respondents with purposive sampling as a sampling technique. Secondary data is obtained from the Central Bureau of Statistics, books, theses, theses, journals. Importance Performance Analysis (IPA), Coordinate Kartesius and Customer Satisfaction Index (CSI) as data analysis techniques. The results of the study are that service quality has an influence on the factors of the tendency of millennial society and infrastructure to strengthen the influence of the factors of millennial society's tendency towards service quality in improving market function. The results of this study were obtained from a survey analysis of millennial visitors in traditional markets in Banyumas, namely the perception of millennial society can change towards traditional markets if the quality of service for market managers and traders can be improved in a better direction. Thus it will encourage millennial communities to visit and shop in traditional markets.